Case for exploring compressor water injection for airport emission reduction - Block Novelo, David Alejandro; Igie, Uyioghosa (ASME, 2017)
The increasing world population, higher accessibility to air transportation, coupled with new low-cost airline models has resulted in an unprecedented increase in demand for civil aviation. The industry is currently experiencing a global increase of operational civil aircraft at a rate of 5–6% annually. This growth suggests a vibrant future for the industry, however, the environmental implications and the footprint is worth considerable attention given the expected scale of growth in the industry and the possible side effects to human health. The stakeholders involved, some of which include: airports and airline operators, jet engine and airframe manufacturers and various government bodies, are introducing measures in order to mitigate the increase in certain emissions and hence their impact. This study focuses on one of the many existing approaches targeting the reduction in gaseous emissions, predominantly nitrogen oxides (NOx). This is through compressor water injection that is estimated to reduce NOx emissions by almost half under certain ambient conditions and water-to-air ratio. Apart from reviewing this technology, the study, more importantly, presents the ideas in relation to other major existing approaches/concepts. It would be observed that compressor water injection can be more readily applied to the existing infrastructure when compared to other approaches. This technique is one of the most promising methods for reducing NOx emissions, an area of particular importance given that modern engines, though more thermally efficient, operate at higher pressure ratios and flame temperature, both of which enhance nitrogen oxides formation. One of the main contributions of this paper is the categorisation of existing approaches focused on reducing aircraft-borne airport emissions. Different technologies and operational changes are classified according to the key pollutants that they target with respect to the landing and takeoff cycle based on 11 different engine types. These gaseous-emissions mitigating approaches are analyzed based on their individual merits, limitations and feasibilities. Compressor water injection is re-introduced here as a more readily applicable solution despite its technological challenges, many of which can be better resolved with today’s knowledge
Keywords: Compressors; Underground injection; Emissions